Miejsce i funkcje współczesnego rachunku kosztów w systemie informacyjnym zarządzania przedsiębiorstwem - Szydełko, Alfred (The Place and Functions of Modern Cost Accounting in Information Management System, 2005)
In subject of literature we haven't got uniform views on place and functions of cost accounting in information management system. This article shows relation analysis between cost accounting, financial accounting and management accounting. The integrating processes in accounting work mainly in cost accounting area, which is currently treated as an autonomous system.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 343-348